Assessment of Patient Satisfaction Level to Dental Health Care Services in Indonesia - Fuad Husain Akbar; Syahrir Pasinringi; Abdul Hair Awang (Association of Support to Oral Health Research (APESB), 2022)
Objective: To know the level of patient satisfaction with dental healthcare services in Bantaeng, Indonesia. Material and Methods: This pilot pathfinder survey was conducted at Dental and Oral Health Services in Bantaeng and Pa'jukukang Sub-districts of Bantaeng Regency of South Sulawesi Indonesia. The Short-Form Patient Satisfaction Questionnaire (PSQ-18) scaled was used and it consists of 18 questions and seven subscales. The t-test and ANOVA were used with a significance level set at 5% (p<0.05). Results: The female participation (72.8%) was greater than the male (27.2). Regarding age, 74.6% were <40 years, 21.1% were between 40-60 years old and 4.4% were over 60 years old. On the subscale of technical quality, there was significant value in the age variable (p=0.45), education level (p=0.031), job (p=0.026), waiting time (p=0.46), distance to dentist=0.026), and location (p=0.007). There were significant values on the interpersonal aspect subscale that were present at age (p=0.016), education level (p=0.038), and occupation (p=0.007). The highest satisfaction score was found on the technical quality subscale (13.04 ± 1.75) and the lowest satisfaction score was seen on the general satisfaction subscale (4.11 ± 1.75). There was a significant difference between the value of patient satisfaction with age, education, and occupation. Conclusion: Patients from the District Bantaeng and Pa'jukukang Bantaeng regency of South Sulawesi were more satisfied with the service provided. The highest satisfaction score was found on the technical quality subscale and the lowest satisfaction score was found in the general satisfaction subscale.